The Degree of Diabetic Wounds Affects Kidney Function Damage - Windartik, Emyk; Rahmawati, Ima; Jariyah, Ita Ainun; Merbawani, Raras; Lestari, Indah; Andriyanto, Arief; Ro’ifah, Ifa (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: The peripheral neuropathy is the cause of hospitalization for patients with diabetes mellitus (DM) and damages kidney function due to the circulatory system with high sugar levels. High sugar levels in DM patients with diabetic wounds can trigger glomerular damage resulting in the decrease of kidney function.Purpose: This study aims to analyze the relationship between the degree of diabetic wounds and kidney functions in patients with DM.Methods: A cross-sectional study was conducted on 723 DM patients who experienced diabetic wounds in a hospital in Mojokerto, East Java, Indonesia. A purposive sampling technique was used to recruit the samples. The data of this study were medical records of diabetic patients. A simple linear regression test was employed to analyze the data.Results: The result showed that the degree of diabetic wound was significantly related to kidney function damage (p=0.000). The relationship between the degree of diabetic wounds and the decline in kidney function was shown by an R-squared value of 0.768, meaning that the degree of diabetic wound affected the decline of kidney function by 76.8%, while the 23.2% was affected by other factors.Conclusion:The degree of diabetic injury affects the decline of kidney function in DM patients by 76.8%. Nurses should do health promotion about controlling blood sugar levels in DM patients with the prevention of four pillars of diabetes, including education, nutrition, physical activity, and stress.Â